1993
DOI: 10.1002/jca.2920080206
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of demographics and motivations of highly committed whole blood and platelet donors

Abstract: To compare donor demographics and motivations for donation, we surveyed 159 consecutive whole blood donors (WD) and 146 consecutive plateletpheresis donors. All donors had donation experiences of at least 2 gallons (i.e., 16 previous donations). Evaluation of answers to fixed-response and open-ended questions revealed no difference between the two groups in age, type of wages, compensation by employer, "time off" for donation, and church or volunteer organization memberships. The two groups differed in that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 10 publications
1
32
0
2
Order By: Relevance
“…As there may be far fewer women among PPDs, samples may be too small to make interesting comparisons [17,22]. Our results revealed that, of WBDs, it was primarily the women who donated thinking that a member of their family (or a friend) could need blood, who generally considered there to be a strong need for blood products, and who viewed giving blood as a positive thing to do that required little effort.…”
Section: Men and Women: Different Profilesmentioning
confidence: 61%
See 3 more Smart Citations
“…As there may be far fewer women among PPDs, samples may be too small to make interesting comparisons [17,22]. Our results revealed that, of WBDs, it was primarily the women who donated thinking that a member of their family (or a friend) could need blood, who generally considered there to be a strong need for blood products, and who viewed giving blood as a positive thing to do that required little effort.…”
Section: Men and Women: Different Profilesmentioning
confidence: 61%
“…Seven percent of divorced PPDs selected "My coworkers also give blood" and their WBD counterparts chose "My religious practice or convictions have encouraged me to donate" more often (4%) than other sub-categories. Around 10% of younger (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and single PPDs chose "Blood donation is a tradition in my family" while a similar proportion of male PPDs chose "I feel recognition from people around me" as an important motivator. Lastly, only 3% of PPDs in their thirties (30)(31)(32)(33)(34)(35)(36)(37)(38)(39) and those with a low education chose "When I see posters and advertising" as a motivator.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Una de las posibles respuestas como motivación para donar sangre era "Los regalos tras la donación" que obtuvo tan solo un 1.3% (2), lo que está en consonancia con estudios previos que sostienen que los incentivos materiales no son una buena estrategia de captación ya que apenas influyen en el posible donante 15 e incluso pueden llegar a ejercer un efecto negativo al hacer que el individuo no tenga en cuenta los beneficios sociales y en consecuencia, done con menos frecuencia 13,14 .…”
Section: Recien Artículo Original Revista Científica De Enfermeríaunclassified